Evaluating User Learning Behavior in Relation to the Use of Multimedia Hyper-Lecture Package with a Tracking Facility - Yee, Yin Yii; Sow, Seah Kuan (INTI International University, 2007)
E-learning packages are increasingly using audio and video presentations in addition to graphical and textual media to enhance the learning experience of students. However, a current assessment of the literature suggest that little has been done to evaluate the effects of this type of delivery on learning. In this paper, we discuss the design and development of a multimedia hyper-lecture systems, which incorporates a computational method for tracking a user’s interaction with the application. This system servers as a tool to investigate the behavior of users in relation to characteristics associated with learning styles such as activist, theorist, reflector and pragmatist, in a multimedia environment.